Cyclic RGDyk-conjugated LMWH-taurocholate derivative as a targeting angiogenesis inhibitor - Adulnirath, Asarasin; Chung, Seung Woo; Park, Jooho; Hwang, Seung Rim; Kim, Ji-Young; Yang, Victor C.; Kim, Sang Yoon; Moon, Hyun Tae; Byun, Youngro (ELSEVIER SCIENCE BV, 2012)
LMWH-taurocholate derivative (LHT7) has been reported as a novel angiogenesis inhibitor, due to its ability to bind to several kinds of growth factors, which play critical roles in tumor angiogenesis. In this study, we have highlighted the enhanced antiangiogenic activity of LHT7, by using cyclic RGDyk (cRGD), a targeting moiety that was chemically conjugated to LHT7 via amide bond. The SPR study revealed that cRGD-LHT7 bound to alpha(v)beta(3) integrin as strongly as cRGD, and it bound to VEGF as strongly as LHT7. Importantly, in vitro anti-angiogenesis studies revealed that cRGD-LHT7 had a significant inhibition effect on HUVEC tubular formation. Finally, cRGD-LHT7 showed a greater inhibitory efficiency on the tumor growth in the U87MG xenograft model than the original LHT7, which was owed to its ability to target the tumor cells. All of these findings demonstrated that cRGD-LHT7 targeted alpha(v)beta(3) integrin-positive cancer cells and endothelial cells, resulting in a greater anti-angiogenesis effect on the solid tumors. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: TUMOR ANGIOGENESIS; INTEGRIN ALPHA(V)BETA(3); HEPARIN; CANCER; VEGF; GROWTH; DRUG; PROGRESSION; DELIVERY; MICE